2021
DOI: 10.3389/fmars.2021.669528
|View full text |Cite|
|
Sign up to set email alerts
|

Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters

Abstract: Chronic low-frequency noise from commercial shipping is a worldwide threat to marine animals that rely on sound for essential life functions. Although the U.S. National Oceanic and Atmospheric Administration recognizes the potential negative impacts of shipping noise in marine environments, there are currently no standard metrics to monitor and quantify shipping noise in U.S. marine waters. However, one-third octave band acoustic measurements centered at 63 and 125 Hz are used as international (European Union … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Missed detections may occur when the selected background frequencies and/or the signal frequencies are overwhelmed by sounds from other sources. The influence of anthropogenic sound sources such as vessel noise is prevalent at the Olympic Coast, Cordell Bank, and Channel Islands recording locations, with large container ships being particularly dominant and producing sound at frequencies that overlap with blue and fin whale calls (McKenna et al, 2013;Haver et al, 2018;Haver et al, 2020;Haver et al, 2021). Therefore, the potential for masking could be high in these locations resulting in an underestimate of call presence and reduced communication space for these species (Clark et al, 2009;Hatch et al, 2012;Cholewiak et al, 2018).…”
Section: Additional Parameters To Considermentioning
confidence: 99%
See 2 more Smart Citations
“…Missed detections may occur when the selected background frequencies and/or the signal frequencies are overwhelmed by sounds from other sources. The influence of anthropogenic sound sources such as vessel noise is prevalent at the Olympic Coast, Cordell Bank, and Channel Islands recording locations, with large container ships being particularly dominant and producing sound at frequencies that overlap with blue and fin whale calls (McKenna et al, 2013;Haver et al, 2018;Haver et al, 2020;Haver et al, 2021). Therefore, the potential for masking could be high in these locations resulting in an underestimate of call presence and reduced communication space for these species (Clark et al, 2009;Hatch et al, 2012;Cholewiak et al, 2018).…”
Section: Additional Parameters To Considermentioning
confidence: 99%
“…Therefore, the site-specific and seasonal levels in background noise need to be heavily considered when applying this technique to different sites and interpreting those results. Cross-referencing blue and fin whale vocalizations, and vessel noise frequency bands with vessel tracking data could assist in a broader understanding of the low-frequency soundscape drivers at the NRS sites (Haver et al, 2020;Haver et al, 2021).…”
Section: Additional Parameters To Considermentioning
confidence: 99%
See 1 more Smart Citation
“…Ten listening stations with data in April of 2019 and 2020 were used to understand changes in vessel noise presence metrics related to early-COVID shutdowns. Previous studies have used both 63-Hz and 125-Hz one-third octave bands as representative of noise from marine vessel tra c (Haver et al, 2021). This study summarized sound pressure levels in the 125 Hz one-third octave band, which is representative of a wide range of vessel sizes.…”
Section: Listening For Vesselsmentioning
confidence: 99%
“…Although AIS was not designed with research or conservation planning in mind (Robards et al, 2016), many studies have demonstrated the multifaceted bene ts of this monitoring data (Welch et al, 2022). Listening for underwater vessel noise using passive acoustic monitoring provides information on vessel presence (Haver et al, 2023;Kline et al, 2020), speci c noise output (ZoBell et al, 2021(ZoBell et al, , 2023, and cumulative noise added to the marine environment (Haver et al, 2021). The spatial scale of hearing vessel noise depends on sound propagation conditions in the local environment, while the temporal scale varies by instrumentation limitations and project goals.…”
Section: Introductionmentioning
confidence: 99%